Clinical evaluation of fixed prosthetic restorations requiring replacement and associated patient- and restoration-related factors: a cross-sectional study - Senem Güneykaya; Tuhfe Çelikkol; Ayşe Taş; Nelli Agbulut; Gülsüm Sayın Özel (BMC Oral Health, 2026)
Abstract Background Fixed prosthetic restorations may deteriorate through biological, mechanical, and patient-related factors. This study described the clinical condition of fixed prosthetic restorations presenting for replacement, and examined the patient-, restoration-, and clinician-related factors associated with their clinical acceptability, using modified United States Public Health Service (USPHS) criteria. Methods This cross-sectional study included 395 tooth-supported fixed prosthetic restorations from 346 patients aged 18 years or older, in function for at least 6 months and clinically indicated for replacement, at three centres of a single university. No restorations remaining in satisfactory service were sampled. Two independent, calibrated examiners applied modified (California Dental Association) USPHS criteria: anatomical form, marginal adaptation, color match, marginal discoloration, secondary caries, and surface roughness, resolving disagreements by consensus. A restoration was classified overall unacceptable if any single domain was unacceptable. Because 36 patients contributed more than one restoration, associations were assessed by generalized estimating equations with patient-level clustering ( p < 0.05). Results Metal–ceramic restorations were the most common material, followed by zirconia; most had been in function for 6–10 years or longer. Unacceptable ratings were most frequent for secondary caries (55.2%) and anatomical form (50.1%), and 75.9% of restorations were unacceptable in at least one domain. After accounting for within-patient clustering, restoration age was associated with all six USPHS domains ( p < 0.05; Cramér’s V 0.21–0.34) and toothbrushing habits with four (anatomical form, color match, secondary caries, surface roughness). Bruxism was associated with anatomical form and color match, restoration type with marginal adaptation, institution with two domains, and clinician with marginal discoloration. Smoking, material, location, and attendance frequency showed no significant associations. In the multivariable model restoration age remained associated with overall acceptability ( p = 0.012), although no individual category reached significance. Conclusions Among restorations presenting for replacement, restoration age and toothbrushing habits showed the most consistent associations with clinical deterioration, whereas other factors were associated with individual domains only. Because only restorations already indicated for replacement were examined, these findings describe associations within a selected clinical population and cannot be interpreted as predictors of restoration survival or longevity. Regular follow-up and reinforcement of oral hygiene remain reasonable clinical recommendations.